Jungle 2 Jungle - Reilly, Brian; Pasquin, John (USA: Walt Disney Picture [production company] ; Kuala Lumpur : Berjaya HVN [distributor], 1998)
Successful broker Michael Cromwell travels to Amazon jungle to get his wife's signature on divorce papers,when he discovers the surprise of his life
Editor, Michael A. Stevenson ; screenplay, Bruce A. Evans, Raynold Gideon
Cast : Tim Allen, Martin Short
Keywords: Comedy films; Children's films; Wildlife films